Identifikasi Senyawa Metabolit Sekunder Ekstrak Daun Turi (Sesbania grandiflora L) Dengan Menggunakan Pelarut Etanol, Etil asetat dan n-Heksan - Ahlan Sangkal; Hamidah Sri Supriati; Ayu S. Jamal (Jurnal Sains dan Kesehatan, 2021)
Turi (Sesbania grandiflora L) is native to Southeast Asia. This plant is used as a medicinal plant and also a vegetable. Turi (Sesbania grandiflora L) is a plant that is efficacious for the treatment of various diseases such as analgesic, antipyretic, diuretic and laxative. The purpose of this study was to identify the content of secondary metabolites in turi leaf extract extracted with ethanol, ethyl acetate and n-hexane as solvents. This research was conducted in two stages, namely extraction by maceration method using ethanol, ethyl acetate and n-hexane as solvents. And the identification stage of secondary metabolites consisting of identification of alkaloids, steroids, terpenoids, saponins and flavonoids. The results showed that the positive ethanol and ethyl acetate extracts contained flavonoids, saponins, terpenoids and steroids, while the negative n-hexane extract contained secondary metabolites.